MANAJEMEN PERUBAHAN: STUDI PADA REFORMASI PELAYANAN PERIZINAN DI KOTA YOGYAKARTA - Kurnia Nur Fitriana (Yogyakarta State University, 2015)
This study aims to analyze the management of change in the licensing service reforms undertaken by the Government of the city of Yogyakarta. Urgency of the study was conducted because of the constraints faced in the process of reform of the licensing service in the city of Yogyakarta and potential resistance from the aspect of human resources (HR) to respond to changes. This study used a qualitative approach. Reform of licensing services at the Licensing Agency of Yogyakarta directed to the arrangement of three aspects: First, reforming the institutional and human resources; Secondly, the implementation aspects of licensing services; and Third, aspects of organizational innovation with the development of the use of information technology. The impacts of the implementation of information technology-based licensing service at Licensing Agency of Yogyakarta, has had a positive impact in terms of efficiency, effectiveness and permits the achievement of performance targets Licensing Agency of Yogyakarta and have public accountability. Management changes in the reform of the licensing service in the city of Yogyakarta to do with the model of planned change through three stages, namely unfreezing, changing and moving, and refreezing. Keywords: bureaucratic reformation, licensing service, Yogyakarta City Government